Komunikasi dan Pariwisata: Analisis Pengelolaan Wisata dalam Meningkatkan Wisatawan Batu Badaun di Mandailing Natal - Rasyidin; Ritonga, Muhammad Husni (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to determine how the strategy of the Mandailing Natal Regency Tourism and Culture Office in increasing domestic tourist visits and foreign tourists to Batu Badaun Beach, because it is known that tourism marketing strategies are very important for the growth of regional tourism. This research uses descriptive qualitative methodology, with data collected through observation, interviews, and documentation. Furthermore, it was analyzed using Miles and Huberman. SWOT analysis was applied with Integrated Communication Theory (IMC). The results showed that the Tourism Office of the Tourism and Culture Office promotes tourism online, print media, radio, brochures, booklets, pamphlets, and journals. Marketing is hampered by limited services, infrastructure, and tourism development funds. Media, organizational organizational and group communication with tourism managers and traders, and individual approaches with community leaders are used by the Mandailing Natal Regency Tourism and Culture Office. The author also argues that the development plan for the Batu Badaun Beach tourism area in Sikapas Village, Muara Batang Gadis Sub-district, Mandailing Natal Regency must pay attention to the concerns and aspirations of the community.